DEVELOPMENT OF THEMATIC E-MODULES BASED ON AL-QUR'AN VERSES TO IMPROVE STUDENT LEARNING OUTCOMES - Eva’atussalamah Eva’atussalamah; Agus Zainul Fitri; Choiruddin Choiruddin (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2022)
The lack of effectiveness of government thematic books taught in elementary schools currently tends to lead to low learning outcomes during the covid-19 pandemic. However, the problem seems to be getting worse because of the unavailability of suitable learning media to support the teaching and learning process from home for educators and students during the covid-19 pandemic. Therefore, this research was conducted to develop thematic e-module media based on Al-Qur'an verses to improve student learning outcomes during the covid-19 pandemic. This study was developed based on the Borg & Gall model with data collected using questionnaires, tests, and documentation and analyzed through the Independent Sample T-test. The results show sig.(2-tailed) of 0.000 < 0.05. then Ha is accepted while H0 is rejected. It was found that the average student learning outcomes improved to 83.4 and learning completeness by 83.33% after receiving treatment in the form of thematic e-module media based on Al-Qur'an verses. This shows that this subjects is feasible to be implemented as a learning medium because of its effectiveness in improving the learning outcomes of fifth-grade students of MI Al-Hidayah 02 Betak.